Secondary Metabolites from the Mangrove Ecosystem-Derived Fungi Penicillium spp.: Chemical Diversity and Biological Activity - Guojun Zhou; Jin Cai; Bin Wang; Wenjiao Diao; Yu Zhong; Shaodan Pan; Weijia Xiong; Guolei Huang; Caijuan Zheng (Marine Drugs)
Mangrove ecosystems have attracted widespread attention because of their high salinity, muddy or sandy soil, and low pH, as well as being partly anoxic and periodically soaked by tides. Mangrove plants, soil, or sediment-derived fungi, especially the Penicillium species, possess unique metabolic pathways to produce secondary metabolites with novel structures and potent biological activities. This paper reviews the structural diversity and biological activity of secondary metabolites isolated from mangrove ecosystem-derived Penicillium species over the past 5 years (January 2020–October 2024), and 417 natural products (including 170 new compounds, among which 32 new compounds were separated under the guidance of molecular networking and the OSMAC approach) are described. The structures were divided into six major categories, including alkaloids, polyketides, terpenoids, benzene derivatives, steroids, and other classes. Among these natural products, the plausible biosynthetic pathways of 37 compounds were also proposed; 11 compounds have novel skeleton structures, and 26 compounds contain halogen atoms. A total of 126 compounds showed biological activities, such as cytotoxic, antifungal, antibacterial, anti-inflammatory, and α-glucosidase-inhibitory activities, and 11 compounds exhibited diverse biological activities. These new secondary metabolites with novel structures and potent bioactivities will continue to guide the separation or synthesis of structurally novel and biologically active compounds and will offer leading compounds for the development and innovation of pharmaceuticals and pesticides.